Avaliação do projeto público “Paragominas: Município Verde” sob a ótica das mudanças climáticas - SILVA, Laryssa de Cassia Tork da (Universidade Federal do Pará, 2019)
The Paragominas municipality, located in the northeastern portion of Para state, has a history that expresses very well the environmental problem of Amazon deforestation, integrating the first two major deforester’s lists released by MMA in 2008 and 2009. After Paragominas inclusion on the list, local farmers began to suffer various penalties such as restrictions to agricultural credit and reduction of the consumer market. In early 2008, the municipal government held a local seminar seeking for solutions. At the end of the event, the organizations adhered to the Zero Deforestation Pact, aiming to eliminate deforestation and forest degradation from the adoption of sustainable practices. Thus, inaugurating "Paragominas: Green City" project. After two years suffering from restrictions and embargoes, goals accomplishment and demands adequacy, such as deforestation reduction to less than 40 km² in a year and CAR fulfill in more than 80% of county farms, caused the removal of Paragominas municipality from deforester’s list and the project "Paragominas: Green County" was widely reported in the media as responsible for bringing many benefits to the city, becoming the reference environmental standpoint. It is believed, however, that "Paragominas: Green City" project is actually a reflection of the new legal demands established by the Brazilian Federal Government to combat illegal logging and climate change. In other words, it is part of a larger goal to identify new pathways, and practical solutions to fight back changes brought by climate variability specially by reducing greenhouse gases emissions in particular from land use land cover change on the Brazilian Amazon. In this sense, the present work aims to evaluate the "Paragominas: Green City" project as a practical adaptation to climate variability into the context of mitigation of global climate change. The methodology involves two steps: gathering and analysis of bibliographic and documentary references and application of semi-structured interviews with the main stakeholders, based on the application of the Index of Utilidad de Prácticas de Adaptación (IUPA)presented and adapted from the paper "IUPA: a tool for the evaluation of the general usefulness of practices for adaptation to climate change and variability, "prepared by Debels et al. (2009), focusing on variables of effectiveness, efficiency, social participation, sustainability and replicability of the project. However, the "Paragominas: Green City" project can be clearly understood as a result of new environmental demands, resulting from the need for new alternatives to the impacts of climate variability. The initial goal of the project was just the removal of Paragominas municipality from the of embargoed list. Although due to the great repercussion and achieved results, the project gained new directions, becoming an important tool in combating the greenhouse gases emission problem. Nevertheless, it still needs some adjustments to truly be classified as a powerful climate adaptation practice with ample potential to combat and mitigate the changes associated to climate change